Sn/Nano-SiC Composite Electrodeposition Technology - Chu, Hongtao; Zhao, Yue; Su, Liqiang; Zhang, Jinqiu; An, Maozhong (Asian Journal of Chemistry, 2013)
A Sn/nano-SiC composite electrodeposition technology was studied. The effects of electrodeposition behaviour were investigated by the concentration of main salt, the concentration of methylsulfonic acid, current density etc. The influence law of particles content in the solution on the particle content in Sn/nano-SiC composite coating was also studied. The results show that, when the concentration of Sn2+ was 0.21-0.24 mol/L, the concentration of methylsulfonic acid was 90-120 g/L, current density was 1.5-2.5 A/dm2, there was a higher deposition rate in the electrodeposition process, current efficiency and throwing power were both above 90 %. The nano-SiC content in composite coating was increased with SiC content in bath increasing, when it was 5 g/L, SiC content in composite coating was highest.